The Development of Discovery Learning-based Module to Improve Students’ Scientific Literacy - Indah Slamet Budiarti; Triwiyono Triwiyono; Florentina Maria Panda (Jurnal Pembelajaran Fisika, 2021)
In learning science, it is necessary to have a learning model that can integrate scientific literacy skills. This study aimed to develop discovery learning-based module to improve students’ scientific literacy. We used R & D research that adapts the 4-D model device development procedure, namely define, design, develop, and disseminate. Product assessment was carried out after revision stage I by 3 media experts, 3 material experts, and 1 SMA YPPK Taruna Bakti teacher. To determine student responses, the product was tested for feasibility and readability on 5 X grade students of SMA YPPK Taruna Bakti through a limited trial. The product was revised and tested again through a broad trial on 16 students. The revision through experts’ comments and students’ initial responses has affected the readability, feasibility, and usability of the developed Newton’s Law module. There were no students who have high scientific literacy. Students who have low scientific literacy were 13 and students who have moderate scientific literacy were 3. It can be said that the module cannot significantly improve students’ scientific literacy because of the online learning environment.Keywords: Discovery learning, Modul, Newton’s Law, Scientific literacyDOI: http://dx.doi.org/10.23960/jpf.v9.n1.202107